The problem with Opaque AI - Asher Austen Fainman (The Thinker)
The ability to uncover, evaluate and predict causality is fundamental in disciplines of inquiry, such as law. Effective adoption of Artificial Intelligence (AI) applications in domains in which legally significant  consequences result will depend heavily on the user’s ability to provide explanons and contest decisions.